HOMOCYSTEINE AND KIDNEY'S FUNCTIONAL STATUS OF THE CHILDREN WITH THE NEPHROTIC SYNDROME - L.T. Faizova; V.V. Alatyrtsev; G.F. Gordeeva; I.V. D'yachenko; E. Jargal; M.I. Bakanov; M.Ya. Studenikin; A.N. Tsygin (Педиатрическая фармакология, 2008)
The authors presented the data on the homo cysteine serum concentration in the children with nephrotic syndrome. They established the high rate of hyper homo cysteinemia in the nephritic syndrome, but the degree of the homocysteine concentration increase is largely due to the kidney's functional status rather than the activity of the disease. They also discuss the pathogenetic role of hyper homo cysteinemia in the event of the chronic nephritic pathology.Key words: homo cysteine, nephrotic syndrome, children.